IMPROVING THE ATTRACTION OF FOREIGN DIRECT INVESTMENT IN THE MANUFACTURING INDUSTRY (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article provides feedback on the role and importance of foreign direct investments in the manufacturing industry of our country, and the work being done to attract them. Evaluation of its capabilities and determination of development prospects are also emphasized